Dampak Media Sosial Bagi Generasi Muda - Yurlena Halawa; Dermawan Zebua (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
The rapid development of social media has brought significant changes to the lives of young people, affecting social, psychological, and educational aspects. Social media is no longer merely a means of communication and entertainment but has become a primary platform for young people to access information and express themselves. This study aims to analyze the impact of social media use on the younger generation. A quantitative approach with a descriptive research design was employed. Data were collected through the distribution of questionnaires to young people as research respondents. The findings indicate that social media provides positive impacts, including easier access to information, improved communication, and enhanced creativity. However, excessive use of social media also leads to negative effects, such as mental health problems, reduced quality of face-to-face social interactions, and poor time management. Therefore, efforts to enhance digital literacy and promote responsible social media use are essential to maximize its benefits while minimizing its adverse effects.